Microbial effects of cold-pressed Sacha inchi oil supplementation in rats - Tepparit Samrit; Supawadee Osotprasit; Athit Chaiwichien; Phawiya Suksomboon; Supanan Chansap; Thitikul Suthisintong; Narin Changklungmoa; Pornanan Kueakhai (PLoS ONE, 2025)
Oil supplements have various benefits for metabolism, particularly Sacha inchi oil (SI), which is rich in polyunsaturated fatty acids (PUFAs) such as ω-3 and fat-soluble vitamins. However, the impacts of oil supplements on gut health remain unclear. The aim of this study was to compare the effects of an SI supplement with those of lard oil (LO), known for its high saturated fatty acid content, and a normal diet on gut health in male Sprague Dawley rats for 12 consecutive weeks. Fecal DNA was used to assess gut microbiota diversity and species abundance, diversity, and function prediction. Colon tissue from each rat was examined for colon crypt depth and histology. Rats administered the LO supplement exhibited higher dysbiosis than those administered the SI supplement, with the LO supplement influencing the relative abundance of various bacteria at the genus level. A KEGG analysis was conducted to examine the effects on metabolic pathways, revealing that the SI supplement promoted carbohydrate metabolism while reducing immune system activity. In contrast, the LO supplement increased replication, repair, and translation activities. A histological analysis of the colon tissues showed no significant alterations in crypt depth or lesions in all groups, indicating that neither supplement induced adverse structural changes in the gut. The results of this study suggest that SI supplementation modulates the gut microbiota, thereby enhancing gut health and metabolic function.